Propuesta de Evaluación de Gestión de Residuos y el impacto ambiental de la atención de los servicios de salud en el Área de Salud de Curridabat de la Caja Costarricense del Seguro Social en el 2023-2024 (Repertorio Científico, 2023)
Health care and environmental sustainability: proposed evaluation of waste management and environmental impacts of health care services in Curridabat Health Area in Caja Costarricense del Seguro Social between 2023-2024. The effects of health services are essential for public health as they are producing serious impact on hospital budgets, increasingly, larger budgets are required to care for patients with diseases associated with environmental pollution and although the actions are to protect and restore health, the generation of waste and byproducts that are generated are considerable (WHO, 2015). In this sense, the health sector can play an important role in mitigating the generation of health care waste. Therefore, the objective is to establish the environmental impact of healthcare waste management in the Curridabat Health Area between the years 2023-2024. A longitudinal descriptive observational study will be conducted using a convenience sample of a health area of the Caja Costarricense del Seguro Social institution; in this case belonging to the Curridabat Health Area existing as of August 2022, including the 5 EBAIS sites, Dental Services, Pharmacy, sterilization center and administrative offices between 2023 and 2024. The information will be collected directly by the researchers or intermediaries of the health center on common solid waste and recycling collection days through the application of the Evaluation Protocol sheets prepared by DIGECA of MINAE, specifically protocols 8, 10, 11 and 12. The environmental performance matrix will be prepared for 2023 with the calculation of the corresponding indicators for the health area under study. Correlation will be made with the data of the consultations provided by the health center and/or services performed. An analysis of the environmental impact of the waste collected will be performed.